1995
DOI: 10.1002/1097-4679(199507)51:4<532::aid-jclp2270510410>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Attributions of shy persons in romantic relationships

Abstract: The present research examined attributions of shy persons in the interpersonal situation of romantic relationships. Two hundred fifteen undergraduate psychology students were administered the Beck Depression Inventory (BDI), the Social Avoidance and Distress Scale (SAD), and the Romantic Relations Attributions Questionnaire (RRAQ). Correlations are reported for both the SAD and the BDI with the RRAQ. Partial correlations of the SAD with the RRAQ with depression removed also are reported. Results suggest that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 15 publications
3
16
0
Order By: Relevance
“…This awareness may in turn inhibit these individuals even more, creating an even higher level of arousal in social interactions (Alm, 2007) and make them more vulnerable in relation to others. Moreover, shy individuals attribute various situations described as attributing a negative outcome to internal causes rather than to external ones, whereas non-shy persons reverse this attributional pattern (Anderson, 1991;Johnson, Aikman, Danner, & Elling, 1995). In summary, although previous findings are not entirely consistent concerning the relationship between shyness and causal attribution of negative and positive outcomes in social situations, there seems to be a tendency for shy individuals to attribute reactions to stable internal causes rather than to external (Alm, 2007).…”
Section: Shynesssupporting
confidence: 84%
See 1 more Smart Citation
“…This awareness may in turn inhibit these individuals even more, creating an even higher level of arousal in social interactions (Alm, 2007) and make them more vulnerable in relation to others. Moreover, shy individuals attribute various situations described as attributing a negative outcome to internal causes rather than to external ones, whereas non-shy persons reverse this attributional pattern (Anderson, 1991;Johnson, Aikman, Danner, & Elling, 1995). In summary, although previous findings are not entirely consistent concerning the relationship between shyness and causal attribution of negative and positive outcomes in social situations, there seems to be a tendency for shy individuals to attribute reactions to stable internal causes rather than to external (Alm, 2007).…”
Section: Shynesssupporting
confidence: 84%
“…The episodes related to boys in the interviews and observations were more associated with unstructured classroom activities, where repeated negative comments dominated. Shy adolescents are unpopular and have low peer status as both friends and romantic partners (Fordham & Stevenson-Hinde, 1999;Johnson et al, 1995;Rubin et al, 2006). To a greater degree, girls' status is more connected to intimate friendships than boys (Parker & Seal, 1996;Rubin et al, 2006), and female adolescent friendships are less stable than those of boys and are characterized by a "best-friend" dyad (Maccoby, 2002).…”
Section: Gender Of the Bullymentioning
confidence: 55%
“…While these studies examine explanations of the cause of negative situations, it may be argued that these attributions are related to interpretations regarding the cost or consequences of negative events, given that both pertain to the meaning that individuals attach to events, and both may have implications for the individuals' perception of the self and the future. Although results along each of the specific attributional dimensions have shown variability between studies, it has frequently been found that people high in social anxiety are more likely than those low in social anxiety to explain failures in social situations as being the result of internal, stable, and/or global factors (Alfano, Joiner, & Perry, 1994;Anderson & Arnoult, 1985;Arkin, Appelman, & Burger, 1980;Bruch & Belkin, 2001;Bruch & Pearl, 1995;Girodo, Dotzenroth, & Stein, 1981;Hope, Gansler, & Heimberg, 1989;Johnson, Aikman, Danner, & Elling, 1995;Johnson, Petzel, & Johnson, 1991;Teglasi & Fagin, 1984;Teglasi & Hoffman, 1982). Furthermore, in accordance with data indicating that inflated probability and cost estimates are specific to negative social, as opposed to negative non-social situations (Foa et al, 1996;Lucock & Salkovskis, 1988), several researchers have found that social anxiety is unrelated to attributions made for failure situations of a non-interpersonal nature (Anderson & Arnoult, 1985;Bruch & Belkin, 2001;Teglasi & Hoffman, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Wilson and Rapee (2005b) found that within-treatment reductions in the extent to which individuals with social phobia believed that negative social events were indicative of negative self-characteristics were predictive of improvements in social phobia symptomatology in the longer-term. These results are largely consistent with those from attributional studies, which indicate that social anxiety is associated with a tendency to explain social failures as being the result of internal (features of the self), stable (likely to persist), and/or global (likely to affect outcomes in a range of situations) factors (Alfano, Joiner & Perry, 1994;Anderson & Arnoult, 1985;Arkin, Appelman, & Burger, 1980;Bruch & Belkin, 2001;Girodo, Dotzenroth, & Stein, 1981;Heimberg et al 1989;Johnson, Aikman, Danner & Elling, 1995;Johnson, Petzel & Johnson, 1991;Taylor & Wald, 2003;Teglasi & Fagin, 1984;Teglasi & Hoffman, 1982; see also Hope, Gansler, & Heimberg, 1989).…”
mentioning
confidence: 99%